2016
DOI: 10.1016/j.jss.2015.01.058
|View full text |Cite
|
Sign up to set email alerts
|

5W+1H pattern: A perspective of systematic mapping studies and a case study on cloud software testing

Abstract: A common type of study used by researchers to map out the landscape of a research topic is known as mapping study. Such a study typically begins with an exploratory search on the possible ideas of the research topic, which is often done in an unsystematic manner. Hence, the activity of formulating research questions in mapping studies is ill-defined, rendering it difficult for researchers who are new to the topic. There is a need to guide them kicking off a mapping study of an unfamiliar domain. This paper pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…The primary indicators assessed include (1) "why" establishes the rationale for the initiative and which dimensions it contributes, e.g., environment, social, economic, and governance; (2) "what" details the main planning domains of the intervention of SEC solutions, e.g., buildings, transportation, ICT and integrated infrastructures, and energy and technology; (3) "how" describes how the plan was implemented using various tools and mechanisms, e.g., governance, planning mechanisms, monitoring and evaluation, funding, and context and process; (4) "who" includes information about the institution and its partners responsible for conducting the initiative, e.g., decisionmakers, experts, utilities, end-users, community organisations, financial institutions, and the private sector; (5) "where" includes information on the scale of the development, e.g., individuals, buildings, neighbourhoods, districts, cities, transportation; (6) "when" describes the time horizon for the implementation of the projects, e.g., short, medium, and long-term. The Kipling approach was selected, as it provides a systematic approach to problemsolving and project planning for information gathering and deconstructing the literature [33]. Content analysis is a widely utilised scientific approach for the empirical and structured analysis of documents and communications [34], which is then examined, classified, and summarised.…”
Section: Methodsmentioning
confidence: 99%
“…The primary indicators assessed include (1) "why" establishes the rationale for the initiative and which dimensions it contributes, e.g., environment, social, economic, and governance; (2) "what" details the main planning domains of the intervention of SEC solutions, e.g., buildings, transportation, ICT and integrated infrastructures, and energy and technology; (3) "how" describes how the plan was implemented using various tools and mechanisms, e.g., governance, planning mechanisms, monitoring and evaluation, funding, and context and process; (4) "who" includes information about the institution and its partners responsible for conducting the initiative, e.g., decisionmakers, experts, utilities, end-users, community organisations, financial institutions, and the private sector; (5) "where" includes information on the scale of the development, e.g., individuals, buildings, neighbourhoods, districts, cities, transportation; (6) "when" describes the time horizon for the implementation of the projects, e.g., short, medium, and long-term. The Kipling approach was selected, as it provides a systematic approach to problemsolving and project planning for information gathering and deconstructing the literature [33]. Content analysis is a widely utilised scientific approach for the empirical and structured analysis of documents and communications [34], which is then examined, classified, and summarised.…”
Section: Methodsmentioning
confidence: 99%
“…This work formulates the research questions based on the 5W+1H model,() also known as the Kipling method . This method is used in other systematic reviews of software engineering and answers the questions: why, what, how, by whom, where, and when. The research questions of this mapping study are as follows: RQ1Why is testing performed in MapReduce programs? RQ2What testing is performed in MapReduce programs? RQ3How is testing performed in MapReduce programs? RQ4By whom, where, and when is testing performed in MapReduce programs? …”
Section: Planning Of the Mapping Studymentioning
confidence: 99%
“…A systematic mapping study is reported in two research papers, [6] [12], using the 5W+1H model for reporting systematic reviews. Studies are categorized based on research questions, authors and countries, research objectives, research ideas, patterns of papers on different types of cloud service and publication type, immediacy of article citation, and article inter-relevance.…”
Section: Related Workmentioning
confidence: 99%